The nature and emotional-stylistic functions of paraphrasing in mass media (Eurasian Journal of Philology Science and Education, 2015)
The given article considers the figurative nature of paraphrasing as the artistic technique used in mass media. The ways of differentiating paraphrasing from such expressive means, as metaphor, metonymy,synecdoche, comparison, epithet, euphemism, phraseology are in the focusof the author. Mass media is one of the sources of information, so, the function of paraphrasing is very important. Paraphrasing represents a dynamic equivalent and conveys an important thought expressed in a source text— if necessary, at the expense of literality. Paraphrased texts attract readers’ attention, and they are frequently used by journalists.
Keywords: paraphrase; description; phraseology; comparison; stylistic figure; figurative meaning; semantic structure